Autonomie vůle v dědickém právu v ČR a Německu - Rajsigl, David; Dobešová, Lenka, 1972-; Masarykova univerzita. Katedra občanského práva (2006)
Tato diplomova prace se zabyva principem autonomie vule v dedickem pravu v CR a Nemecku. V jednotlivych kapitolach jsou rozebrany konkretni projevy teto zasady na strane zustavitele a dedice. V zaveru prace je zpracovan exkurs do ceske upravy autonomie vule v dedickem pravu de lege ferenda.
This thesis deals with the principle autonomy of Will in the Law of Succession in the Czech Republic and in Germany. In the particular chapters there are parsed concrete demonstrations of this principle on the part of testator and inheritor. At the end of work there is processed excursus to the Czech regulation of autonomny of will in the law of inheritance de lege ferenda.
Vedoucí práce: Lenka Dobešová.
Diplomová práce (Mgr.)--Masarykova univerzita, Právnická fakulta, 2006.
Keywords: autonomie vůle; dědické právo; inheritance and succession; principle of autonomy of the will; diplomové práce